2020
DOI: 10.1055/s-0040-1716081
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age and the Delay before Surgery on the Outcomes of Intercostal Nerve Transfers to the Musculocutaneous Nerve: A Retrospective Study of 232 Cases of Posttraumatic Total and Near-total Brachial Plexus Injuries

Abstract: Introduction Posttraumatic brachial plexus injuries are devastating, as the brain and spinal cord are disconnected from the upper limb. Restoration of elbow flexion has been widely recognized as the primary objective of nerve reconstruction. In the absence of utilizable (ruptured) root stumps in the neck, one has recourse only to nerve transfers. The direct transfer of intercostal nerves to the musculocutaneous nerve is one of the techniques that has been commonly employed over the past four decades. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Reconstruction of brachial plexus injury (BPI) is challenging, and patients with BPI restoration of elbow functions, 1 followed by shoulder functions, are given priority. The shoulder functions have traditionally been restored by the spinal accessory nerve (SAN) to suprascapular nerve (SSN) transfer in an irreparable root avulsion in BPI.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction of brachial plexus injury (BPI) is challenging, and patients with BPI restoration of elbow functions, 1 followed by shoulder functions, are given priority. The shoulder functions have traditionally been restored by the spinal accessory nerve (SAN) to suprascapular nerve (SSN) transfer in an irreparable root avulsion in BPI.…”
Section: Introductionmentioning
confidence: 99%
“…We found the better results were those who were 30 years old or younger. At present, we are largely reserving this technique of reanimation surgery for younger patients based on the theory that nerve regeneration and clinical results are more optimum (Bhatia et al, 2020) although in the future, we may expand our indications to include older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pages et al [ 54 ] showed that brachial plexus injury could be functionally or structurally restored by nerve reconstruction, with early nerve surgery yielding satisfactory functional outcomes. Patients younger than 30 years old and those operated upon earlier than 6 months from the accident having better functional recovery [ 55 ] through intercostal nerve transfers [ 56 ]. Generally, patients with distal nerve transfers had faster motor recovery and better elbow flexion power than patients with intercostal nerve transfers.…”
Section: Achievements and Progress In Clinical Diagnosis And Neurores...mentioning
confidence: 99%